2001
DOI: 10.1016/s0370-2693(01)00380-x
|View full text |Cite
|
Sign up to set email alerts
|

Transition quadrupole moments in γ-soft nuclei and the triaxial projected shell model

Abstract: Transition probabilities of the ground-state bands in γ-soft nuclei are studied for the first time using the triaxial projected shell model approach. It is observed that the angular-momentum dependence of the transition quadrupole moment Q t is related to the triaxial deformation of the nuclear mean-field potential. The introduction of the γ-degree of freedom in the shell model basis is shown to have a little influence on the constant behavior of the low-spin Q t in a well-deformed nucleus. However, the increa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 21 publications
(41 reference statements)
3
21
0
Order By: Relevance
“…In the present calculation, we choose G 1 and G 2 such that the calculated gap parameters reproduce the experimental mass differences. The values G 1 and G 2 , choosen in the present work, are G 1 = 20.82 and G 2 = 13.58 and are consistent with our earlier investigations [11,15,28,29,30,31,32,33,34].…”
Section: Introductionsupporting
confidence: 93%
“…In the present calculation, we choose G 1 and G 2 such that the calculated gap parameters reproduce the experimental mass differences. The values G 1 and G 2 , choosen in the present work, are G 1 = 20.82 and G 2 = 13.58 and are consistent with our earlier investigations [11,15,28,29,30,31,32,33,34].…”
Section: Introductionsupporting
confidence: 93%
“…In the present work, we also evaluate the intraand inter-band electromagnetic transition probabilities, and it is shown that the deformation used in the present work provides a better agreement for the transition calculations in comparison to our earlier work on the ground-state configuration only [26]. The TPSM approach has already been discussed in our earlier publications [12][13][14][15][16][17], and in the following we shall provide only a few details of the model that are relevant to the discussion of the results.…”
mentioning
confidence: 70%
“…We have also evaluated quadrupole transition probabilities along the yrast band in the framework of TPSM [27]. The standard effective charges (e π = 1.5e and e ν = 0.5e) are used in the calculation for 76 Ge, and later for all other nuclei studied in the present work.…”
Section: Results Ofmentioning
confidence: 99%